To simplify the expression, we can distribute the coefficients:
12(x+4) + 14(4x-2) = 12*x + 12*4 + 14*4x - 14*2
Simplifying further:
= 12x + 48 + 56x - 28
Combining like terms:
= (12x + 56x) + (48 - 28)
= 68x + 20
The simplified expression in mixed number form is 68x + 20.
Add: 12(x+4)+14(4x−2) . Answer should be in mixed number form
7 answers
Add: 1/2(x+4)+1/4(4x−2) . Answer should be in mixed number form
To simplify the expression, we can distribute the coefficients:
1/2(x+4) + 1/4(4x-2) = 1/2*x + 1/2*4 + 1/4*4x - 1/4*2
Simplifying further:
= 1/2*x + 2/2 + 4/4*x - 2/4
= 1/2*x + 1 + x - 1/2
Combining like terms:
= (1/2*x + x) + (1 - 1/2)
= 3/2*x + 1/2
The simplified expression in mixed number form is 1 1/2x + 1/2.
1/2(x+4) + 1/4(4x-2) = 1/2*x + 1/2*4 + 1/4*4x - 1/4*2
Simplifying further:
= 1/2*x + 2/2 + 4/4*x - 2/4
= 1/2*x + 1 + x - 1/2
Combining like terms:
= (1/2*x + x) + (1 - 1/2)
= 3/2*x + 1/2
The simplified expression in mixed number form is 1 1/2x + 1/2.
sorry that is wrong
I apologize for the mistake. Let's redo the simplification:
1/2(x+4) + 1/4(4x−2)
= 1/2 * x + 1/2 * 4 + 1/4 * 4x - 1/4 * 2
= 1/2x + 2/2 + 4/4x - 2/4
= 1/2x + 1 + x - 1/2
= (1/2x + x) + (1 - 1/2)
= 3/2x + 1 - 1/2
= 3/2x - 1/2
The simplified expression in mixed number form is 1 1/2x - 1/2.
1/2(x+4) + 1/4(4x−2)
= 1/2 * x + 1/2 * 4 + 1/4 * 4x - 1/4 * 2
= 1/2x + 2/2 + 4/4x - 2/4
= 1/2x + 1 + x - 1/2
= (1/2x + x) + (1 - 1/2)
= 3/2x + 1 - 1/2
= 3/2x - 1/2
The simplified expression in mixed number form is 1 1/2x - 1/2.
now make it not a mixed number please
To convert the expression back into an improper fraction, we can find a common denominator and add the fractions:
3/2x - 1/2 = (3x - 1)/2
So the simplified expression, not in mixed number form, is (3x - 1)/2.
3/2x - 1/2 = (3x - 1)/2
So the simplified expression, not in mixed number form, is (3x - 1)/2.